THINKING ABOUT THINKING: SHIFTING THE CONVERSATION ABOUT GENERATIVE AI - Leslie, Christopher (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2026)
This article proposes a conceptual shift about generative AI (genAI) in language teaching and research. There are very real concerns about potential harms from genAI, including invasion of privacy, erosion of creativity, theft of intellectual property, cheating on assignments, and degradation of the environment. However, genAI is here to stay, and educators should shift their attention to helping students and colleagues use genAI tools productively in a way that affirms our common humanity. The history of technology has already long demonstrated that devices do not invariably cause an inevitable and uniform transformation of the social world; indeed, human values and aspirations have often shaped the use of technology. GenAI is no different. Reviving the concept of metacognition, which has already been shown to help improve computer-based instruction, this paper demonstrates practical ways that English language educators can promote uses of genAI that foster critical thinking and innovation.